Sources of forage adjusted to temperature changes for wintering cows in drylot - M. McKee; K. Kimple; D.R. Ames; C.L. Willms; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1978)
Cows in mid-to-late gestation gained weight when fed either milo stover silage or alfalfa hay-wheat straw but lost weight when the forage source was milo-stover bales. When supplemented with additional corn grain as temperature decreased, cows receiving milo stover stilage or alfalfa hay-wheat straw gained more eight, and cows receiving milo stover bales lost less weight than cows receiving the same forages but fed to NRC (1976) requirements.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Temperature; Drylot; Forage